2018
DOI: 10.1021/acs.jafc.8b02611
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Capsaicin and Hesperidin Reduces the Effectiveness of Each Compound To Decrease the Adipocyte Size and To Induce Browning Features in Adipose Tissue of Western Diet Fed Rats

Abstract: We explored the potential of hesperidin and capsaicin, separately and in combination, to induce white adipose tissue (WAT) browning and to help body weight management in Western diet-fed rats. Adult male Wistar rats were fed for 8 weeks with Western diet and treated daily with hesperidin (100 mg/kg/day), capsaicin (4 mg/kg/day), hesperidin (100 mg/kg/day) + capsaicin (4 mg/kg/day), or the vehicle. Hesperidin and capsaicin separately, but not (or to a lesser extent) the combination, resulted in a decreased size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Finally, it is worth mentioning that in this work the dose of maqui was scaled-down from the polyphenol intake recommended as beneficial in humans by the Predimed Study [45,46]. This is important because several phenolic compounds such as resveratrol, quercetin, cyanidin-3-glucoside (C 3 G), capsaicin, hesperidin have green tea extract have been described as inducers of BAT activity or WAT browning but in most cases the dietary supplementation was performed using high doses and only the active compounds [9,10,11,12,13,117,118,119,120,121].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth mentioning that in this work the dose of maqui was scaled-down from the polyphenol intake recommended as beneficial in humans by the Predimed Study [45,46]. This is important because several phenolic compounds such as resveratrol, quercetin, cyanidin-3-glucoside (C 3 G), capsaicin, hesperidin have green tea extract have been described as inducers of BAT activity or WAT browning but in most cases the dietary supplementation was performed using high doses and only the active compounds [9,10,11,12,13,117,118,119,120,121].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding nutritional inputs, we recently demonstrated that low-protein diets and the cooked-tomato sauce called “sofrito” are able to induce Ucp1 expression in WAT, thus indicating a browning phenotype [6,7]. In the same way, other authors published that high-fat diets, bioactive compounds and prebiotics can also induce browning in WAT [9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Hesperidin decreased the size of adipocytes and induced the formation of multilocular and positive-UCP1 and CIDEA brown-like adipocytes. Besides the induction browning, hesperidin also enhanced the expression of Ucp1 in BAT [ 221 ]. In contrast, it has been recently published a study where not hesperidin but its monoglycosyl has the capacity to induce brown-like adipocyte formation in HFD-fed mice [ 222 ].…”
Section: Flavanonesmentioning
confidence: 99%
“…Traditional medicinal plants have huge natural compound resources and better safety in drug development and application. At present, several studies revealed the effective natural compounds of antiobesity are extracted from botany, including sulforaphene [12], daidzein [13], quercetin [14], hesperidin and capsaicin [15], methylated cereal flavonoid [16], and dietary phenolic [17], indicating the natural products are a great choice as potential candidates for treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%